A review of membrane distillation process: - Before, during and after testing - N.A.S, Muhamad; Nadzirah, Mohd Mokhtar; Rosmawati, Naim; Lau, Woei Jye; A.F., Ismail (Penerbit Universiti Malaysia Pahang, 2019)
Membrane Distillation (MD) has garnered much interest as a reassured technology in separation and purification processes. MD separation process used difference of vapor pressure between surfaces of porous hydrophobic membrane as a driving force. The process allows only transport of water vapour molecules through membrane pores. This paper focuses on expectation of MD treatment process primarily for readers who lack knowledge on membrane process. A brief overview of MD before treatment process is given which includes membrane materials, membrane preparation techniques, membrane characteristics, module, and configuration. Membrane performance during treatment process was highlighted. The major drawback of MD which is membrane fouling was also emphasized in this paper.